2012
DOI: 10.1016/j.cellsig.2011.12.005
|View full text |Cite
|
Sign up to set email alerts
|

IQGAP1 and its binding proteins control diverse biological functions

Abstract: IQGAP proteins have been identified in a wide spectrum of organisms, ranging from yeast to humans. The most extensively studied family member is the ubiquitously expressed scaffold protein IQGAP1, which participates in multiple essential aspects of mammalian biology. IQGAP1 mediates these effects by binding to and regulating the function of numerous interacting proteins. Over ninety proteins have been reported to associate with IQGAP1, either directly or as part of a larger complex. In this review, we summaris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
248
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(254 citation statements)
references
References 121 publications
(173 reference statements)
5
248
0
1
Order By: Relevance
“…This pathway regulates cell polarity and migration through modulating activities of the Rho family of GTPases (Rho, Rac, and CDC42), which all interact with IQGAPs directly (35,36,42). Importantly, IQGAP1 can recruit the actin assembly proteins neural Wiskott-Aldrich syndrome protein (N-WASP) and mDia1 to coordinate receptor activation with FA assembly, which is critical to the control of cell adhesion and migration (43)(44)(45).…”
Section: Rspo-mentioning
confidence: 99%
See 2 more Smart Citations
“…This pathway regulates cell polarity and migration through modulating activities of the Rho family of GTPases (Rho, Rac, and CDC42), which all interact with IQGAPs directly (35,36,42). Importantly, IQGAP1 can recruit the actin assembly proteins neural Wiskott-Aldrich syndrome protein (N-WASP) and mDia1 to coordinate receptor activation with FA assembly, which is critical to the control of cell adhesion and migration (43)(44)(45).…”
Section: Rspo-mentioning
confidence: 99%
“…Of the many putative proteins identified (Table S1), two candidates, IQGAP1 and IQGAP3, were particularly notable for their pleiotropic roles in signal transduction (35,36). The three highly homologous IQGAPs (IQGAP1-3) contain multiple domains that bind to and modulate the activity of a plethora of signaling molecules, including Rho GTPases, MAP kinase (MAPK), and components of Wnt pathway E-cadherin, β-catenin, and adenomatous polyposis coli (35,36). We first confirmed that full-length LGR4 interacts with IQGAP1 as well as with IQGAP2 and IQGAP3 by co-IP analysis ( Fig.…”
Section: Rspo-mentioning
confidence: 99%
See 1 more Smart Citation
“…To define the mechanism by which GPR161 induces proliferation, migration, and invasion, we focused on an adherens junction-localized scaffold protein that is related to GPCR signaling. IQGAP1 regulates a vast array of cellular functions through interactions with proteins such as E-cad, Neural Wiskott-Aldrich syndrome protein (N-WASP), Cdc42, and the exocyst complex (19). IQGAP1 has been reported to interact with βArr2, a scaffold protein that binds to activated GPCRs and regulates signaling and receptor endocytosis (20).…”
Section: Gpr161 Induces Migration and Invasion Of Mammary Epithelial mentioning
confidence: 99%
“…IQGAP1 is a multifunctional adaptor protein involved in the coordination of diverse cellular processes, including receptor activation, regulation of MAPK signaling, activity of small GTPases, the regulation of cytoskeletal remodeling, and assembly of cell junctions (23)(24)(25)(26). IQGAP1 controls microtubule and actin cytoskeletal dynamics via interactions with small GTPases Rac1 and Cdc42.…”
mentioning
confidence: 99%